COMPARAÇÃO DAS FORÇAS DE DEFLEXÃO LIBERADAS ENTRE OS FIOS ORTODÔNTICOS ESTÉTICOS E SUA RELAÇÃO COM O REVESTIMENTO - Santoro, Miller Zaroni (2011)
The aim of this study was to compare the forces of deflection in vitro between aesthetic and wire NiTi wires, to check the maximum force and plateau region and determine its correlation with the diameter of the wire with and without coating. Ten trials were conducted in seven brands of bows pre-skirted, six-wire aesthetic (InVu (I), Optis (O), Flexy Super Elastic Esthetic (FSEE), Orthocosmetic Elastinol (OE), Niticosmetic (N), and Pro Form Coated Nitanium (PFCN)) and a superelastic NiTi wire (Nitinol Super Elastic (NSE), applying The test is three-point bending, associated with universal machine EMIC. We developed a device with ceramic brackets (Transcend), whose strings were arrested for elastic modular, and obtained the values of the force deflection at 3.0, 2.0 and 1.0 mm. The diameter of the wires with and without coating were measured using digital especímetro Micromaster. The analysis of variance with a criterion (p <0.05) showed significant difference between the wires and post-hoc Tukey test determined that the force at 3mm deflection for wire O<OE=PFCE<FSEE=NSE<I. The paired t-test compared the strength of deflection (2-1mm) in the plateau region and showed that the wires O, FSEE and N showed constant forces. The wire N showed the largest diameter among the samples, while NSE wires and O, minors. The Pearson correlation coefficient showed that there was a correlation between the diameter of the wire and the force of deflection. It can be concluded that there are differences between the forces produced by the wires and aesthetic that force is directly proportional to the diameter of the uncoated wire for all peaks, ie the larger the diameter, the greater the force produced.